Book Review: Viking Age Brew, by Mika Laitinen - Merryn Dineley (EXARC Journal)
What did ale and beer taste like in the past? How was it made? What sort of equipment did they use and what were the ingredients? The answers to all of these questions, and more, can be found in this book. Archaeologists, experimental archaeologists, brewing historians and anyone interested in ancient technologies will find this book invaluable as an easily accessible study and explanation of pre-industrial beer brewing techniques.